The Role of IL-17 Promotes Spinal Cord Neuroinflammation via Activation of the Transcription Factor STAT3 after Spinal Cord Injury in the Rat - Shaohui Zong; Gaofeng Zeng; Ye Fang; Jinzhen Peng; Yong Tao; Keke Li; Jingmin Zhao (Mediators of Inflammation)
Study Design. In this study, we investigated the role of IL-17 via activation of STAT3 in the pathophysiology of SCI. Objective. The purpose of the experiments is to study the expression of IL-17 and related cytokines via STAT3 signaling pathways, which is caused by the acute inflammatory response following SCI in different periods via establishing an acute SCI model in rat. Methods. Basso, Beattie, and Bresnahan hind limb locomotor rating scale was used to assess the rat hind limb motor function. Immunohistochemistry was used to determine the expression levels of IL-17 and p-STAT3 in spinal cord tissues. Western blotting analysis was used to determine the protein expression of p-STAT3 in spinal cord tissue. RT-PCR was used to analyze the mRNA expression of IL-17 and IL-23p19 in the spleen tissue. ELISA was used to determine the peripheral blood serum levels of IL-6, IL-21, and IL-23. Results. Compared to the sham-operated group, the expression levels of IL-17, p-STAT3, IL-6, IL-21, and IL-23 were significantly increased and peaked at 24 h after SCI. The increased levels of cytokines were correlated with the SCI disease stages. Conclusion. IL-17 may play an important role in promoting spinal cord neuroinflammation after SCI via activation of STAT3.